A behavioural-theory-based qualitative study of the beliefs and perceptions of marginalised populations towards community volunteering to increase measles immunisation coverage in Sabah, Malaysia - Hazeqa Salleh; Richard Avoi; Haryati Abdul Karim; Suhaila Osman; Prabakaran Dhanaraj; Mohd Ali ‘Imran Ab Rahman (MDPI, 2023)
The development of the measles-containing vaccine (MCV) has rendered measles a largely preventable disease. In the state of Sabah in Malaysia, a complete course of measles immunisation for infants involves vaccinations at the ages of six, nine, and twelve months. However, it is difficult for marginalised populations to receive a complete course of measles immunisation. This present study used behavioural theory (BT) to examine the beliefs and perceptions of a marginalised population towards community volunteering as a method of increasing the immunisation coverage of measles. Marginalised populations living in Kota Kinabalu, Sabah, more specifically, Malaysian citizens living in urban slums and squatter areas, as well as legal and illegal migrants, were extensively interviewed in person for this qualitative study. The 40 respondents were either the parents or primary caregivers of at least one child under the age of five. The components of the Health Belief Model were then used to examine the collected data. The respondents had poor awareness of the measles disease and perceived the disease as not severe, with some even refusing immunisation. The perceived barriers to receiving vaccinations included a nomadic lifestyle; issues with finances, citizenship status, language, and weather; failing to remember immunisation schedules; a fear of health care personnel; having too many children; and a lack of female autonomy in vaccine decision-making. However, the respondents were receptive towards community-based programmes and many welcomed a recall or reminder system, especially when the volunteers were family members or neighbours who spoke the same language and knew their village well. A few, however, found it awkward to have volunteers assisting them. Evidence-based decision making may increase measles immunisation coverage in marginalised populations. The components of the Health Belief Model validated that the respondents lacked awareness of the measles disease and viewed it and its effects as not severe. Therefore, future volunteer programmes should prioritise increasing the receptivity and self-control of marginalised populations to overcome barriers that hinder community involvement. A community-based volunteer programme is highly recommended to increase measles immunisation coverage.